2023
DOI: 10.1002/alr.23138
|View full text |Cite
|
Sign up to set email alerts
|

IL‐17A facilitates type 2 inflammation in a modified eosinophilic chronic rhinosinusitis mouse model

Abstract: BackgroundEosinophilic chronic rhinosinusitis (ECRS) is predominantly characterized by nasal type 2 inflammation. The pathogenesis of this condition is complex. High levels of IL‐17A are associated with eosinophil infiltration in some inflammatory diseases and contribute to the severity and insensitivity of corticosteroid therapy for chronic rhinosinusitis.MethodsIn the first experiment, we constructed a modified ECRS mouse model using four groups of mice: phosphate‐buffered saline (PBS)‐sensitized and nasal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Currently, there are no monoclonal antibodies targeting inflammatory cytokines of type 1 and type 3 to treat patients with CRS. Some studies have shown that IL‐17A can enhance the expression of type 2 cytokines and eosinophil infiltration in ECRS or NP mouse model, which might provide a new option for the treatment of CRS with biologics 135,136 …”
Section: Characteristics Of Mucin Hypersecretion In Different Endotyp...mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are no monoclonal antibodies targeting inflammatory cytokines of type 1 and type 3 to treat patients with CRS. Some studies have shown that IL‐17A can enhance the expression of type 2 cytokines and eosinophil infiltration in ECRS or NP mouse model, which might provide a new option for the treatment of CRS with biologics 135,136 …”
Section: Characteristics Of Mucin Hypersecretion In Different Endotyp...mentioning
confidence: 99%
“…Some studies have shown that IL‐17A can enhance the expression of type 2 cytokines and eosinophil infiltration in ECRS or NP mouse model, which might provide a new option for the treatment of CRS with biologics. 135 , 136 …”
Section: Characteristics Of Mucin Hypersecretion In Different Endotyp...mentioning
confidence: 99%